UPAYA SEKOLAH DALAM MENINGKATKAN KEDISIPLINAN SISWA MELALUI METODE PENERAPAN REWARD AND PUNISHMENT - Nur Kholis Widodo; Ahmad Muslich; Anip Dwi Saputro (LPPM STAI Muhammadiyah Probolinggo, 2025)
This research aims to know the implementation reward and punishment for improve students discipline of Madrasah Tsanawiyah Al-Imam Prayungan Sawoo Ponorogo. Discipline students through reward and punishment and also for know the factor that affect existence reward and punishment. This research includes field research using a qualitatife approach. Data collection was done by using observation, interview, and documentation method. Data analysis using data reduction, data presentation, and conclusions. This research yielded the findings: 1) application reward and punishment for improve students discipline of Madrasah Tsanawiyah Al-Imam Prayungan Sawoo Ponorogo, namely this should be considered and given in accordance with what the learners do, in order not to give a deterrent effect on the learners. Intensity in the application of rewad and punishment is good because reward and punishment used must be in accordance with behavior of learnes and the rules that have been applied in school and outside school. 2) student discipline through the application of reward and punishment is sufficient of Madrasah Tsanawiyah Al-Imam Prayungan Sawoo Ponorogo is actualliy good enough. It’s just that there still needs to be an to increase discipline because of frequent violation of school rules. 3) factors affecting the application of reward and punishment include : factors of teacher education background, factors of teaching experience, and factors of student motivasion. All greatly affect the use of reward and punishment in improving discipline.